Pacts for Employment and Competitiveness as a Role Model? Their Effects on Firm Performance - John T. Addison; Paulino Teixeira; Katalin Evers; Lutz Bellmann (Institute for the Study of Labor (IZA), 2015)
Pacts for employment and competitiveness are an integral component of the ongoing process of decentralization of collective bargaining in Germany, a phenomenon that has been hailed as key to that nation's economic resurgence. Yet little is known about the effects of pacts on firm performance. The evidence largely pertains to employment and is decidedly mixed. The present paper investigates the association between pacts and a wider set of outcomes wages, employment, investment, productivity, innovation, and survivability in a RDD framework where the controls comprise establishments that negotiated over pacts but failed to reach agreement on their implementation. An extensive set of simulations are run to test for robustness of the key findings of the model. There is no evidence of pacts negatively impacting any of the selected measures of establishment performance. Indeed, the positive effects reported for wages, productivity, and innovation are sustained in simulations.
Keywords: D22; J3; J41; J50; J53; 330; firm performance; concession bargaining; opening clauses decentralization; pacts for employment and competitiveness; regression discontinuity design; Germany